Reducing youth gang violence: the Little Village Gang Project in Chicago - Spergel, Irving A. (Violence prevention and policy series, 2007)
Gang programs -- Project formation -- Entering the field -- Team development -- Social intervention : the outreach youth worker -- Suppression/social control -- Community mobilization -- The project evaluation model -- Changes in social context of program youth -- Life course factors related to self-reported offense/arrest changes -- Project-worker contacts, services, and strategies -- Arrest changes : program and comparison youth -- Arrest changes for different types of gang youth -- Services and outcome -- Gang and community crime change -- Project termination -- Summary